Pengaruh Zakat dan DOK Terhadap Kemiskinan dengan Pertumbuhan Ekomomi Sebagai Variabel Moderasi - Rahman, Nopijal Rizki; Darma, Surya; Amri, Khairul (Yayasan Kawanad, 2024)
This study aims to analyze the influence of Zakat and DOKA on poverty levels using Economic Growth as a moderating variable. Operationalizing panel data from two administrative regions (districts and cities) in Aceh during the 2019-2021 period, the analysis models used are multiple regression and moderated regression analysis. The research results show that Zakat and DOKA in that year had no effect in reducing poverty in Aceh. However, increasing GRDP moderates the influence of Zakat and DOKA on poverty, making these two instruments more effective in reducing poverty levels and increasing economic prosperity.